Collaborative Learning for Professional Development: A Review of Research Methods and Instruments - Sandar, Myo; Kálmán, Orsolya (Journal of Education in Black Sea Region, 2022)
This paper analyzes teacher collaboration research studies based on the research methods and tools used in these studies. As a research methodology, 36 studies were systematically collected from research databases such as EBSCO, ERIC, and search engines such as Google Scholar, based on the selection criteria and themes. Across the studies, they were analyzed using thematic data analysis. According to the findings, collaborative dimensions and activities, teachers’ beliefs and perceptions on their collaboration, teachers’ room to communicate, teacher-to-teacher dialogue, the way teachers work together, and collaborative attitudes are factors in developing research methods and tools used in previous studies of teacher collaboration in schools. Furthermore, previous studies have included various participants such as administrators, teachers, staff members in schools, parents, families, community members and school board members. Informal collaboration, professional learning experience and peer collaboration, school culture, social networks, leadership and school management teams, sustainability in financial and physical conditions of schools and well-planned in-service teacher education programs based on collaborative knowledge creation are factors that influence teacher collaboration. Different conceptual frameworks and instruments have been used to describe teacher collaboration, such as the Teacher Collaboration Improvement Framework (TCIF), the Community of Practice (CoP), the Teacher Collaboration Assessment Survey (TCAS) and the Professional Learning Community-Revised (PLCR) instrument. According to the findings, more research on the term “interprofessional collaboration” in the field of teacher education is required because collaboration between representatives of different professions is now essential for school improvement. The findings of this study have the potential to contribute to future research in teacher collaboration and interprofessional collaboration in education.